Pengaruh Antenatal Class Dengan Teknik Relaksasi Terhadap Kesehatan Mental Ibu Pre Partum - Imelda Fitri; Aurelia Fridons (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2025)
Cases of mental health disorders are the biggest cause of maternal mortality (MMR) in Indonesia. Pregnant women with mental health disorders have risk factors resulting in miscarriage, bleeding during labor and postpartum hemorrhage and mothers are susceptible to infection, fetuses are at risk of premature birth, fetuses are susceptible to infection and Intra Uterine Fetal Death (IUFD). Objectives To determine the effect of antenatal classes with relaxation techniques on the mental health of pre-partum mothers in Pekanbaru City. Method This research is a quantitative study with a quasi-experimental research design using 2 groups, namely the intervention group of 30 people given antenatal class material treatment and applying breathing relaxation techniques for 1 month with 4 meetings and a control group of 30 people who were not given treatment for 1 month. The sampling technique is purposive sampling, primary and secondary data sources, Instruments used are attendance lists, paper questionnaires, KIA books, relaxation music, and antenatal class education modules. The research location is at the Senapelan Health Center and Rumbai Health Center, Data analysis uses univariate analysis and bivariate analysis with SPSS 21 dependent T-test. Results The average mental health score of the control group pretest (84.0) and posttest (71.9) P 0.000 while the intervention group pretest (64.4) and posttest (45.1) P 0.000. There is an effect of antenatal class with relaxation techniques on the mental health of prepartum mothers. The conclusion is that antenatal class with relaxation techniques is a new innovation to improve the mental health of prepartum mothers.